A study on abandoned low cost housing project in Selangor / Nor Azlina Yahaya - Yahaya, Nor Azlina (Faculty of Architecture, Planning and Surveying, 2013)
Abandoned project is one of common phenomena in our Malaysia construction industry. It existences always referred will bring negative impact to developer, contractor and client. In housing project especially low cost type, problem of abandoned project is always occurred. Professional parties that involved such as a Developer, Contractor, Site Supervisor, Quantity Surveyor, Building Surveyor, and Consultant must be responsible by carry out all the constructions works and should be prepared from preliminary stages, during a construction stages and post construction stages. It is to ensure the project is running smoothly and achieved their objective. This research is to study and focused on low cost housing project, whether on project that has been completed or still under construction which implemented by housing developer in Selangor Darul Ehsan and Wilayah Persekutuan Kuala Lumpur. This study shall include literature review, followed with observation on case study, distribution questionnaire and through interview session with housing developer involved in low cost housing project and professional staff.During an analysis of data, the scale of measurement is Likert Scale and the data was presented in average mean index formula, bar graph, description, discussion, pie chart, reporting and scheduled.